Wind power blade outer skin structure integrating electromagnetic shielding and lightning down-conducting functions and preparation method thereof
Patent Information
- Application Number
- CN202611107064.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]为此,本发明的目的在于提供一种集成电磁屏蔽与雷电引下功能的风电叶片外蒙皮结构及其制备方法,其能够全面解决现有雷电防护技术重量大、界面风险高、工艺复杂、功能单一及损伤后性能不可逆失效的问题,满足深远海风电叶片长寿命服役的严苛需求
[0015]1. This invention uses rare earth modified melamine polymer as the matrix and embeds a three-dimensional interconnected carbon nanotube network. A single-layer structure can simultaneously achieve a lightning impulse current carrying capacity of ≥250kA, an electromagnetic shielding efficiency of ≥40dB in the 30MHz-1.5GHz frequency band, UL94V-0 level flame retardancy and photo-thermal dual-mode self-healing function. It can simultaneously replace multiple structures such as metal downconducting mesh, electromagnetic shielding layer and flame retardant coating, and completely solve the technical pain points of existing protection solutions that have single function and require multi-layer superposition.
Smart Images

Figure CN122880672A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional materials technology for new energy equipment, and in particular to an outer skin structure for wind turbine blades that integrates electromagnetic shielding and lightning down-drafting functions, and its preparation method. Background Technology
[0002] Offshore wind turbine blades are constantly exposed to areas prone to thunderstorms, suffering an average of 2-5 lightning strikes per year. Current lightning protection solutions generally employ copper / aluminum conductive mesh embedded in the blade surface, but this approach has several serious drawbacks: the metal mesh increases blade weight by 3-5%, reducing power generation efficiency; the metal-polymer interface is prone to debonding, becoming a source of corrosion and fatigue; additional laying, welding, and insulation treatments are required, resulting in complex processes and low yield rates; and its function is limited, only providing lightning strike conduction without electromagnetic shielding or flame retardant capabilities. Existing research attempts at conductive coating solutions still have significant shortcomings: the conductive network is discontinuous, the lightning current carrying capacity is insufficient (<200kA), the flame retardancy is poor and requires the addition of halogenated flame retardants, and it lacks self-healing capabilities, with conductivity permanently failing after the material is scratched. Currently, there is no technology that can combine CNT three-dimensional networks with rare earth modified melamine polymer (RE-2DPA-1) matrix to simultaneously achieve comprehensive performance of high conductivity, high shielding, intrinsic flame retardancy, and self-healing. Therefore, there is an urgent need for a lightweight, multifunctional, and integrated smart skin structure to replace the traditional metal downlead system. Summary of the Invention
[0003] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.
[0004] Therefore, the purpose of this invention is to provide a wind turbine blade outer skin structure that integrates electromagnetic shielding and lightning down-draft functions, and its preparation method. This structure can comprehensively solve the problems of existing lightning protection technologies, such as large weight, high interface risk, complex process, single function, and irreversible performance failure after damage, and meet the stringent requirements for long-life service of deep-sea wind turbine blades.
[0005] To achieve the above objectives, the first aspect of the present invention provides a wind turbine blade outer skin structure integrating electromagnetic shielding and lightning down-draft functions, comprising a substrate layer and a conductive functional layer embedded within the substrate layer; the substrate layer is composed of rare earth modified melamine polymer; the conductive functional layer is a three-dimensional interconnected carbon nanotube network, the carbon nanotube content is 3-8 wt%, and the three-dimensional interconnected carbon nanotube network forms a continuous conductive path penetrating the thickness direction of the skin structure.
[0006] In the above technical solution, preferably, the three-dimensional interconnected carbon nanotube network forms a coordination anchoring structure with the functional groups of the rare earth modified melamine polymer in the matrix layer through rare earth ions, thereby realizing the dispersion and fixation of carbon nanotubes in the matrix and the enhancement of interfacial bonding.
[0007] In any of the above technical solutions, preferably, the overall thickness of the skin structure is 0.5-1.5 mm, and the density is ≤1.1 g / cm³. 3 .
[0008] In any of the above technical solutions, preferably, the outer surface of the substrate layer is further provided with a surface self-healing layer, which is composed of rare earth modified melamine polymer and has a thickness of 0.1-0.3 mm.
[0009] In the above technical solution, preferably, the rare earth element in the rare earth modified melamine polymer is ytterbium.
[0010] In any of the above technical solutions, preferably, the functional groups of the rare earth modified melamine polymer include carboxyl groups and phenolic hydroxyl groups, and the rare earth ions form coordination bonds with the carbon nanotube surface sites, the carboxyl groups and the phenolic hydroxyl groups, respectively, to form a bridging and anchoring structure of carbon nanotube-rare earth ion-polymer molecular chain.
[0011] In any of the above technical solutions, preferably, after the surface of the skin structure is scratched, the cracks are repaired by 365nm ultraviolet light irradiation or 150℃ heat treatment and the continuity of the conductive path is restored.
[0012] The second aspect of the present invention provides a method for preparing the outer skin structure of a wind turbine blade provided by any of the technical solutions in the first aspect of the present invention, comprising the following steps: (1) mixing carbon nanotubes with a rare earth modified melamine precursor solution and dispersing them by ultrasonication to obtain a uniformly mixed slurry; (2) casting the mixed slurry into a film and then performing hot pressing treatment to form the outer skin structure of the wind turbine blade.
[0013] In the above technical solution, preferably, the temperature of the hot pressing treatment in step (2) is 270℃-350℃, the pressure is 1MPa-5MPa, and the hot pressing time is 8min-15min; during the hot pressing process, the carbon nanotubes and rare earth modified melamine molecular chains are fixed by rare earth ion bridging to form the coordination anchoring structure.
[0014] Compared with existing technologies, the advantages of the wind turbine blade outer skin structure and its manufacturing method that integrate electromagnetic shielding and lightning down-drafting functions provided by this invention are as follows:
[0015] 1. This invention uses rare earth modified melamine polymer as the matrix and embeds a three-dimensional interconnected carbon nanotube network. A single-layer structure can simultaneously achieve a lightning impulse current carrying capacity of ≥250kA, an electromagnetic shielding efficiency of ≥40dB in the 30MHz-1.5GHz frequency band, UL94V-0 level flame retardancy and photo-thermal dual-mode self-healing function. It can simultaneously replace multiple structures such as metal downconducting mesh, electromagnetic shielding layer and flame retardant coating, and completely solve the technical pain points of existing protection solutions that have single function and require multi-layer superposition.
[0016] 2. The density of the skin structure of this invention is ≤1.1g / cm³. 3 Compared with the traditional copper conductive grid solution, it reduces the weight by more than 70%. While achieving better protection capabilities, it significantly reduces the blade's self-weight and operating bending moment, reduces the risk of fatigue damage, and indirectly improves the power generation efficiency and structural safety of wind turbine units.
[0017] 3. This invention constructs a bridging and anchoring structure of "carbon nanotube-rare earth ion-polymer molecular chain" by forming coordination bonds between lanthanide rare earth ions and carboxyl groups, phenolic hydroxyl groups on melamine polymer chains and active sites on the surface of carbon nanotubes. This strengthens the interfacial bonding between the conductive phase and the matrix at the molecular level, eliminating the risk of debonding at the heterogeneous interface from the root. At the same time, the three-dimensional interconnected carbon nanotube network forms multiple redundant conductive paths. Damage to a single point does not affect the overall conductivity. The lightning current carrying capacity far exceeds that of existing conductive coatings, and it can stably adapt to the harsh service environment of high thunderstorm areas at sea.
[0018] 4. This invention achieves intrinsic flame retardancy by relying on the rare earth coordination effect of rare earth modified melamine matrix, with a limiting oxygen index (LOI) ≥ 32%, reaching the UL94V-0 flame retardant level. No additional flame retardant is required, which avoids the performance aging caused by the precipitation of flame retardant and meets the requirements of halogen-free environmental protection, resulting in more stable performance in long-term service.
[0019] 5. Based on the reversible fracture-reconstruction characteristics of rare earth dynamic coordination bonds, after scratches occur on the skin surface, only 365nm ultraviolet light irradiation or 150℃ heat treatment is needed to close the cracks and restore the continuity of the conductive path. The conductivity recovery rate can reach more than 90%, which greatly reduces operation and maintenance costs and downtime losses, and is suitable for the long-term service requirements of deep-sea wind turbine blades with a design life of 100 years.
[0020] 6. This invention adopts a solution blending-hot pressing integrated molding route, which only requires three steps: slurry dispersion, casting, and hot pressing to complete the preparation. No additional layout, welding, and insulation processes are required. It can be directly adapted to the existing compression molding process of wind turbine blades, with a high yield rate and low difficulty in engineering implementation. Attached Figure Description
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:
[0022] Figure 1 This diagram illustrates the layered structure of the outer skin of a wind turbine blade according to an embodiment of the present invention.
[0023] Figure 2 A layered structure diagram of the outer skin structure of a wind turbine blade according to another embodiment of the present invention is shown;
[0024] Figure 3 This diagram illustrates the photothermal self-healing principle of the outer skin structure of a wind turbine blade according to another embodiment of the present invention.
[0025] in, Figure 1 and Figure 2 The correspondence between the reference numerals and component names in the attached drawings is as follows:
[0026] 1. Substrate layer; 2. Conductive functional layer; 3. Surface self-healing layer. Detailed Implementation
[0027] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.
[0028] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.
[0029] like Figure 1 As shown, a wind turbine blade outer skin structure integrating electromagnetic shielding and lightning down-drafting functions according to an embodiment of the present invention includes a substrate layer 1 and a conductive functional layer 2 embedded inside the substrate layer; the substrate layer 1 is composed of rare earth modified melamine polymer (RE-2DPA-1); the conductive functional layer 2 is a three-dimensional interconnected carbon nanotube network, the carbon nanotube content is 3-8 wt%, and the three-dimensional interconnected carbon nanotube network forms a continuous conductive path through the thickness direction of the skin structure.
[0030] In this embodiment, the three-dimensional interconnected carbon nanotube network can construct multiple redundant low-resistance conductive paths inside the skin, which not only ensures rapid conduction capability under high-current lightning impact, but also achieves stable electromagnetic shielding effect over a wide frequency band. The rare earth modified melamine polymer matrix provides excellent mechanical support and weather resistance for the overall structure, while abandoning the traditional metal conductive mesh scheme, achieving lightweight design from the structural source and effectively reducing the operating load on the blades.
[0031] In the above embodiments, preferably, the three-dimensional interconnected carbon nanotube network forms a coordination anchoring structure with the functional groups of the rare earth modified melamine polymer in the matrix layer through rare earth ions, thereby realizing the dispersion and fixation of carbon nanotubes in the matrix and the enhancement of interfacial bonding.
[0032] In this embodiment, the coordination effect of rare earth ions can effectively suppress the aggregation tendency of carbon nanotubes, ensuring that carbon nanotubes can still be uniformly dispersed and form a continuous three-dimensional network at a content of 3-8 wt%. At the same time, a molecular-level bonding interface can be constructed between the conductive phase and the polymer matrix, fundamentally avoiding the risk of heterogeneous interface debonding and delamination, and improving the service stability of the skin structure under long-term fatigue load and marine corrosion environment.
[0033] In any of the above embodiments, preferably, the overall thickness of the skin structure is 0.5-1.5 mm, and the density is ≤1.1 g / cm³. 3 .
[0034] In this embodiment, the thickness range can match the structural strength requirements of the outer skin of the wind turbine blade, ensuring the impact resistance and wear resistance of the skin itself; at the same time, the density of ≤1.1g / cm³ reduces the weight by more than 70% compared with the traditional copper conductive grid scheme, which can significantly reduce the overall weight of the blade, reduce the root bending moment and fatigue loss, and indirectly improve the power generation efficiency of the unit.
[0035] like Figure 2 As shown, in any of the above embodiments, preferably, the outer surface of the substrate layer 1 is further provided with a surface self-healing layer 3, which is composed of rare earth modified melamine polymer and has a thickness of 0.1-0.3 mm.
[0036] In this embodiment, the self-healing surface layer 3 made of pure polymer material can isolate the marine environment medium with high salt spray and high humidity, and protect the internal carbon nanotube conductive network from corrosion; at the same time, the self-healing properties of the surface layer can automatically heal the minor scratches generated during service, prevent the surface damage from spreading inward, and extend the service life of the skin structure.
[0037] In the above embodiments, preferably, the rare earth element in the rare earth modified melamine polymer is ytterbium.
[0038] In this embodiment, trivalent ytterbium ions have abundant coordination sites and suitable ionic radii, which can not only efficiently construct bridging structures between carbon nanotubes and polymer matrices, but also catalyze rapid char formation of the matrix during combustion, and mediate the reversible breaking and reconstruction of dynamic coordination bonds, thus simultaneously achieving multiple functions such as interface strengthening, intrinsic flame retardancy and photothermal self-healing, resulting in the best overall performance.
[0039] In any of the above embodiments, preferably, the functional groups of the rare earth modified melamine polymer include carboxyl groups and phenolic hydroxyl groups, and the rare earth ions form coordination bonds with the carbon nanotube surface sites, the carboxyl groups and the phenolic hydroxyl groups, respectively, to form a bridging and anchoring structure of carbon nanotube-rare earth ion-polymer molecular chain.
[0040] In this embodiment, through the precise coordination of rare earth ions with functional groups on both sides, a stable continuous structure of "conductive phase-bridging center-matrix phase" can be formed at the molecular scale. This not only significantly improves the interfacial bonding strength between carbon nanotubes and the matrix and reduces the risk of interfacial fatigue failure, but also ensures the structural integrity of the conductive network, enabling the skin to maintain stable conductivity and shielding performance under repeated deformation and impact loads.
[0041] like Figure 3 As shown, in any of the above embodiments, preferably, after the surface of the skin structure is scratched, the cracks are repaired and the continuity of the conductive path is restored by irradiation with 365nm ultraviolet light or heat treatment at 150℃.
[0042] In this embodiment, relying on the reversible reconstruction characteristics of rare earth dynamic coordination bonds, scratches on the skin surface and damage to the internal conductive pathways can be repaired under mild light and heat conditions without replacing the entire skin component. This can significantly reduce the operation and maintenance difficulty and downtime cost of deep-sea wind power, and meet the long-cycle service requirements of a 100-year design life.
[0043] Another embodiment of the present invention provides a method for preparing the outer skin structure of a wind turbine blade according to any of the technical solutions in the first embodiment of the present invention, comprising the following steps:
[0044] (1) Carbon nanotubes were mixed with a rare earth modified melamine precursor solution and then ultrasonically dispersed to obtain a uniform slurry;
[0045] (2) The mixed slurry is cast into a film and then subjected to hot pressing to form the outer skin structure of the wind turbine blade.
[0046] In this embodiment, a solution blending combined with hot pressing process is adopted. The process is simple and controllable, which can ensure that carbon nanotubes are uniformly dispersed in the polymer matrix. No additional laying, welding, insulation treatment and other processes are required. It can be directly adapted to the existing wind turbine blade molding production line, which is easy to achieve large-scale mass production and has a higher product yield.
[0047] In the above embodiments, preferably, the temperature of the hot pressing treatment in step (2) is 270℃-350℃, the pressure is 1MPa-5MPa, and the hot pressing time is 8min-15min; during the hot pressing process, the carbon nanotubes and rare earth modified melamine molecular chains are fixed by rare earth ion bridging to form the coordination anchoring structure.
[0048] In this embodiment, the process parameter window ensures that the rare earth modified melamine matrix is fully cured and cross-linked, while promoting the full reaction of rare earth ions with carbon nanotubes and polymer functional groups to form a stable coordination anchoring structure. The molded skin structure has good uniformity in mechanical properties, electrical conductivity and functional characteristics, and high batch stability, which can meet the manufacturing requirements of large-size wind turbine blade skin. Specific Implementation Example 1
[0050] This embodiment provides a wind turbine blade outer skin structure that integrates electromagnetic shielding and lightning strike protection functions, using trivalent ytterbium ions (Yb). 3+ The rare-earth modified melamine polymer is used as the matrix layer 1, and three-dimensional interconnected multi-walled carbon nanotubes (CNTs) are embedded as the conductive functional layer 2. The specific preparation and performance testing are as follows:
[0051] Based on a ratio of 5 wt% carbon nanotubes in the total mass of the composite system, weigh out multi-walled carbon nanotubes and Yb-containing... 3+ The precursor of rare earth modified melamine polymer was added to N-methylpyrrolidone (NMP) solvent and ultrasonically dispersed for 2 hours to obtain a uniformly dispersed slurry. The slurry was cast into a flat mold, with the molding thickness controlled at 1.2 mm, and then sent to a hot press for hot pressing and curing at 300℃ and 2MPa for 10 minutes. After natural cooling, it was demolded to obtain the target skin structure. During the hot pressing process, Yb 3+ It can simultaneously form coordination bonds with the active sites on the surface of carbon nanotubes and the carboxyl and phenolic hydroxyl functional groups on the molecular chain of rare earth modified melamine polymers, constructing a bridging and anchoring structure of "carbon nanotube-rare earth ions-polymer molecular chain", enabling carbon nanotubes to form a three-dimensional continuous conductive network that runs through the thickness direction of the skin inside the matrix.
[0052] The system performance of the skin sample prepared in this embodiment was tested, and the results are as follows:
[0053] Conductivity: The surface resistivity is as low as 0.8Ω / sq, and the conductive path is continuous and stable, which can meet the requirements of rapid conduction of large currents.
[0054] Electromagnetic shielding performance: At a test frequency of 1GHz, the electromagnetic shielding effectiveness reaches 42dB, and the shielding effectiveness is not less than 40dB in the entire frequency band from 30MHz to 1.5GHz.
[0055] Lightning withstand performance: After a 250kA lightning impulse test using a 10 / 350μs standard waveform, the sample surface showed no ablation marks and no overall structural damage.
[0056] Flame retardant performance: Tested according to UL94 standard, the flame retardant rating reaches V-0, the self-extinguishing time is less than 10s, and there is no melting and dripping phenomenon during the combustion process;
[0057] Self-healing performance: After artificially scratching the sample surface to disrupt the surface conductive pathway, it is repaired by irradiation with 365nm ultraviolet light. The conductivity recovery rate can reach 93%, and the surface micro-cracks are basically closed.
[0058] Comparative Example 1 (Traditional Copper Grid Lightning Protection Solution)
[0059] This comparative example adopts a common lightning protection scheme for offshore wind turbine blades, namely, using epoxy resin as the matrix material and embedding a copper conductive mesh to prepare the outer skin structure of the blade. The overall density of this composite structure is 2.8 g / cm³. 3 .
[0060] The comparative sample was tested and its performance compared under the same conditions, and the results are as follows:
[0061] The structure has a high self-weight, with the copper mesh and epoxy composite system having a density of 2.8 g / cm³. 3 When applied to blades, it increases the overall weight by 3-5%, increases the root bending moment and fatigue load, and reduces power generation efficiency.
[0062] The copper mesh and epoxy resin are mechanically interlocked, resulting in weak bonding at the heterogeneous interface. During long-term service, debonding and corrosion are likely to occur, which can become a source of fatigue failure.
[0063] It has no self-healing ability. After surface scratches or lightning damage, the conductive path will be permanently lost. After being struck by strong lightning, the copper mesh is prone to melting and cannot continue to perform the function of lightning conduction. The entire skin needs to be replaced, resulting in high maintenance costs.
[0064] It has a single function, only has the function of lightning strike, and has no intrinsic electromagnetic shielding and flame retardant capabilities. It requires the additional laying of electromagnetic shielding layer and flame retardant coating, and the manufacturing process is complicated with a low yield.
[0065] Technical effects of Example 1 compared to the comparative example
[0066] Compared with the traditional copper mesh + epoxy comparative scheme, the skin structure of Embodiment 1 of the present invention has comprehensive technical advantages, specifically reflected in:
[0067] Significant weight reduction effect: In Example 1, the skin density was only about 1.05 g / cm³. 3 Compared to Comparative Example 1, the weight reduction exceeds 60%, which can effectively reduce the overall weight of the blade, reduce the root bending moment and fatigue loss during operation, and indirectly improve the power generation efficiency of the wind turbine, thus solving the core pain point of increased weight and reduced efficiency of traditional metal mesh.
[0068] Highly integrated functionality: Example 1 achieves four core functions simultaneously through a single-layer structure: lightning strike down conduction, high-efficiency electromagnetic shielding, intrinsic halogen-free flame retardancy, and photothermal dual-mode self-healing. It eliminates the need for additional shielding layers, flame-retardant coatings, or other multi-layer structures, thus completely solving the drawbacks of traditional protection schemes that are single-function and require multiple layers.
[0069] Significantly improved service reliability: Example 1 achieves molecular-level interfacial bonding between the conductive phase and the polymer matrix through rare earth ion coordination anchoring, eliminating the risk of debonding and corrosion failure at the metal-polymer heterostructure interface from the root; the three-dimensional interconnected carbon nanotube network has multiple redundant conductive paths, and there is no structural damage after a strong lightning strike of 250kA, and there will be no problem of metal mesh melting failure, making its long-term service stability more suitable for the harsh environment of the deep sea.
[0070] Lower lifecycle maintenance costs: Example 1 has dynamic and reversible self-healing capabilities. Damage to conductive pathways caused by surface scratches can be restored by gentle ultraviolet irradiation or heat treatment, eliminating the need to replace the entire skin component. This significantly reduces the maintenance difficulty and downtime losses of deep-sea wind power, and can effectively support the long-term service requirements of the blade's 100-year design life.
[0071] The preparation process is simpler and more efficient: Example 1 adopts a solution blending-hot pressing integrated molding process, which eliminates the need for multiple additional processes such as metal mesh laying, welding, and insulation treatment. The preparation process is shorter, the product uniformity and yield are higher, and it can be directly adapted to existing wind turbine blade molding production lines, making it easy to scale up and promote.
[0072] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A wind turbine blade outer skin structure integrating electromagnetic shielding and lightning down-conduction functions, characterized in that, It includes a substrate layer and a conductive functional layer embedded within the substrate layer; The substrate layer is composed of rare earth modified melamine polymer; The conductive functional layer is a three-dimensional interconnected carbon nanotube network, with the carbon nanotube content being 3-8 wt%. The three-dimensional interconnected carbon nanotube network forms a continuous conductive path that runs through the thickness direction of the skin structure.
2. The wind turbine blade outer skin structure integrating electromagnetic shielding and lightning down-drafting functions according to claim 1, characterized in that, The three-dimensional interconnected carbon nanotube network forms a coordination anchoring structure with the functional groups of the rare earth modified melamine polymer in the matrix layer through rare earth ions, thereby achieving dispersion and fixation of carbon nanotubes in the matrix and enhanced interfacial bonding.
3. The wind turbine blade outer skin structure integrating electromagnetic shielding and lightning down-drafting functions according to claim 1 or 2, characterized in that, The overall thickness of the skin structure is 0.5-1.5 mm, and the density is ≤1.1 g / cm³. 3 .
4. The wind turbine blade outer skin structure according to claim 1 or 2, characterized in that, The outer surface of the substrate layer is also provided with a self-healing layer, which is composed of rare earth modified melamine polymer and has a thickness of 0.1-0.3 mm.
5. The wind turbine blade outer skin structure according to claim 4, characterized in that, In the rare earth modified melamine polymer, the rare earth element is ytterbium.
6. The wind turbine blade outer skin structure according to claim 1 or 2, characterized in that, The functional groups of the rare earth modified melamine polymer include carboxyl groups and phenolic hydroxyl groups. The rare earth ions form coordination bonds with the carbon nanotube surface sites, the carboxyl groups and the phenolic hydroxyl groups, respectively, to form a bridging and anchoring structure of carbon nanotube-rare earth ion-polymer molecular chain.
7. The wind turbine blade outer skin structure according to claim 1 or 2, characterized in that, After scratches occur on the surface of the skin structure, the cracks are repaired and the continuity of the conductive path is restored by irradiation with 365nm ultraviolet light or heat treatment at 150℃.
8. A method for preparing the outer skin structure of a wind turbine blade as described in any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Carbon nanotubes were mixed with a rare earth modified melamine precursor solution and then ultrasonically dispersed to obtain a uniform slurry; (2) The mixed slurry is cast into a film and then subjected to hot pressing to form the outer skin structure of the wind turbine blade.
9. The preparation method according to claim 8, characterized in that, The hot pressing process in step (2) is carried out at a temperature of 270℃-350℃, a pressure of 1MPa-5MPa, and a hot pressing time of 8min-15min. During the hot pressing process, carbon nanotubes and rare earth modified melamine molecular chains are fixed by rare earth ion bridging to form the coordination anchoring structure.